Profile of Junior High School Students' Critical Thinking Skills in Solving Geometric Problems Based on Cognitive Styles - Wicaksono, Sadana; Saputra, Ilhammudin; Hamzah, Syamsuddin Noor (SMARTH: Journal of Mathematics Education and Learning, 2025)
Critical thinking is a fundamental competency in mathematics education, particularly in geometry, where students must interpret, analyze, evaluate, and draw inferences from abstract representations; however, these abilities can be influenced by differences in cognitive styles. This study examines the critical thinking profiles of eighth-grade students in solving plane geometry problems by exploring how field-independent (FI) and field-dependent (FD) cognitive styles shape problem-solving processes and outcomes. Cognitive styles were identified using the Group Embedded Figures Test (GEFT), and four students representing FI and FD styles with equivalent mathematical ability were purposively selected. Data were collected through geometry problem-solving tests and semi-structured interviews based on four indicators of critical thinking: interpreting, analyzing, evaluating, and inferring. The results show that FI students demonstrated more systematic, reflective, and autonomous problem-solving approaches, effectively integrating all critical thinking indicators. In contrast, FD students performed adequately in interpretation and basic analysis but experienced difficulties in higher-level processes, particularly evaluation and inference. Inference was identified as the most challenging indicator for students in both cognitive style groups. These findings underscore the influence of cognitive style on students’ critical thinking in geometry and highlight the need for differentiated instructional strategies. Open-ended tasks can support autonomy and deeper reasoning for FI students, while structured scaffolding and guided support are crucial for helping FD students develop higher-order thinking skills and achieve more equitable learning outcomes.